Linking teacher support to achievement emotion profile: the mediating role of basic psychological need satisfaction - Yang, Yang; Gong, Shaoying; Cao, Yang; Qiu, Yin; Xu, Xizheng; Wang, Yanqing (Frontiers in Psychology, 2024)
The current study used a person-centered approach to explore the achievement emotions cooccurrence of college students. It also examined the impact of teacher support on achievement emotion profiles, as well as the mediating effect of need satisfaction. 866 college students participated in the survey. A robust 3-step latent profile analysis was employed to analysis the data. Four profiles of achievement emotions were identified: moderate mixed emotions, blends of high positive emotions, blends of moderate positive emotions and high mixed emotions. Higher perceived teacher support was associated with a greater likelihood of being classified into the blends of moderate positive emotions profile or the blends of high positive emotions profile. Moreover, basic psychological need satisfaction mediated the relationship between teacher support and four emotion profiles. Our findings contribute to a more comprehensive understanding of the role of teacher support in shaping achievement emotion profiles and broaden the application of self-determination theory to explain the mechanism to explain how external support influences emotion profiles.